PENGARUH INTENSITAS KAPITAL TERHADAP TUNJANGAN KECELAKAAN KERJA PADA INDUSTRI MANUFAKTUR DI INDONESIA - Yuda Prawira; Andi Fahmi Lubis (Jurnal Ekonomi dan Pembangunan, 2025)
Increasing of industrial accident in Indonesia from approximateley 97 thousand cases in 2010 soaring about 26% to 123 thousand cases in 2017. This Increasing have to get attention, because it could increase worker compensation that could affect firm profitability. Goals of this research is to analyze impact of firm capital intensity compensation of industrial accident in Indonesia manufacturing industry. Firm with higher capital intensity tend to pay more work accident compensation than firm with less capital intensty through more work accident happen because human contact with machines is more common. With using panel data methods in 2010-2015, this research can prove that labor intensive firm have 44,7% smaller amount of industrial accident compensation thatn non labor intensive firm. Other variable such as worker wage and overtime wage affect positive and significant on industrial accident compensation, while firm’s total worker and firm participation on workers insurance could decrease it significantly. However production worker ratio and economic cycle have positive effect on industrial accident compensation although not significant, while woman worker ratio could r educe it but rather not significant.